A Study of Efficiency of Index Futures, Lead-Lag Relationship, and Speed of Adjustments in India using High-Frequency Data - Danak, Deepak; Patel, Nikunj (Indian Journal of Finance, 2020)
We conducted a rigorous analysis to find out the speed of adjustments in futures and spot indices on NSE NIFTY 50 in short-run as a part of examining the efficiency of the financial futures market in India. Towards that, we undertook the analysis of long-run and short-run efficiencies separately and used Engle-Granger’s error correction mechanism (ECM) so that a clear picture of short-run efficiency in terms of speed of adjustments could emerge. The rigour manifested in the analysis of up to 412538 data points that bred from the choice of five different time intervals spanning from 1-minute to 120-minutes. Most of the price discovery took place in the futures market, and the spot market followed it mostly with a lag of 9 minutes. However, it took 35 minutes to completely return to the desired relationship once a drift had taken place. The increase in the speed of adjustments, as compared to the speed documented in previous studies, could be attributed to the large-scale adoption of the high-frequency (i.e. algorithmic) trading in recent times. Our findings suggested that traders can effectively use the near month contract of Nifty 50 Futures to hedge their open positions in the index or any other stock. At the same time, the market also offers an opportunity to arbitrageurs as the integration did not take place before 9 minutes.